IMPLEMENTASI TRI HITA KARANA SEBAGAI BUDAYA MASYARAKAT BALI DI MELIÃ BALI VILLAS AND SPA RESORT - Nia Kania, - (2009)
This research entitle "Implementasi Tri Hita Karana sebagai Budaya Masyarakat Bali di Meliá Bali Villas and Spa Resort." The background why writer choose this Bali local-wisdom as research material is because these Tri Hita Karana has uniquely as Balinese life philosophy which if it adopted with tourism will resulting the sustainable tourism concept. Tri Hita Karana is the Balinese life philosophy that has meaning as three prosperous creator which is the harmonize between human and God (Parahyangan), the harmonize between humans (Pawongan) and the harmonize between human and environment (Palemahan). The purpose of this research is to analyzing the factors of Meliá Bali Villas and Spa Resort reasons to implementing Tri Hita Karana, analyzing the value of Tri Hita Karana elements which implemented in hotel and evaluating the influence of Tri Hita Karana implementation for Meliá Bali Villas and Spa Resort. This research using descriptive method on qualitative approach For population, researcher using social situation term which consist of place, activities and actors and for sample, researcher using sampling technique purposive technique. The data's in this research reached from many resources through the approach of direct research, interview and secondary data resources and analyzed by Miles and Huberman analyses. The result of this research is the factors affecting Meliá Bali to implement Tri Hita Karana which is as firstly develop concept and platform sustainable development, second is Tri Hita karana criterias were implemented by Meliá Bali Villas and Spa Resort for 96% in veil of management, services, human resources, religi and environment, the third is with implementing Tri Hita Karana, Meliá Bali Villas and Spa Resort has achieve sustainable development and cultural which is measure by great hotel reputation. This research hope to open mind that this Tri Hita Karana may have adapted in other resort or hotel either functioned as local culture keeper for hotel particularly and Indonesia sustain development commonly.